PEMANFAATAN POTENSI LOKAL DESA SLEMPIT DALAM PEMBUATAN SABUN ORGANIK MENGGUNAKAN BAHAN DASAR SUSU SAPI - Shandy Pieter P; Febrian Dinda Wardani; Linda Nur Safitri; Himawati Firdaus; Yahya Luthfiah (Kanigara, 2023)
Village potential is all the power that the village has and has the possibility to be developed so that it can be used as an effort to improve the welfare of the village community. Slempit Village is one of the villages in Kedamean District, Gresik Regency. One of the village potentials owned by Slempit Village is Cow's Milk. Cow's milk in Slempit Village is generally only distributed to distributors. However, if the cow's milk is processed into other processed products, it will be able to add value to the product and also increase the selling value. The Real Work Lecture Team at University of PGRI Adi Buana Surabaya conducted counseling on making organic milk based soap to local mothers. This activity was warmly welcomed by the local residents because in addition to increasing local knowledge about processing milk into soap, it can also be used as a source of livelihood for local residents. This activity was chosen by the aim of besides exploiting local potential, it can also maximize the function of milk for the body.